2017
DOI: 10.1088/1742-6596/861/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Strangeon and Strangeon Star

Abstract: Abstract. The nature of pulsar-like compact stars is essentially a central question of the fundamental strong interaction (explained in quantum chromo-dynamics) at low energy scale, the solution of which still remains a challenge though tremendous efforts have been tried. This kind of compact objects could actually be strange quark stars if strange quark matter in bulk may constitute the true ground state of the strong-interaction matter rather than 56 Fe (the so-called Witten's conjecture). From astrophysical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In this work, B is chosen to be (138 MeV) 4 . Another EoS model considered in this work is the so-called strangeon star model [43]. Unlike the MIT bag model in which quarks are assumed to be de-confined and described by Fermi gas approximation, Lai and Xu suggested that clustering of quarks is possible at the density of a cold compact star since the coupling of strong interaction is not negligible at such energy scale.…”
Section: Strange Star Equation Of Statesmentioning
confidence: 99%
“…In this work, B is chosen to be (138 MeV) 4 . Another EoS model considered in this work is the so-called strangeon star model [43]. Unlike the MIT bag model in which quarks are assumed to be de-confined and described by Fermi gas approximation, Lai and Xu suggested that clustering of quarks is possible at the density of a cold compact star since the coupling of strong interaction is not negligible at such energy scale.…”
Section: Strange Star Equation Of Statesmentioning
confidence: 99%
“…1 Such a quark-cluster star has also been named a strangeon star in Ref. [69]. Lai and Xu attempted to approach the EOS of such quarkcluster star with phenomenological models, i.e., to compare the intercluster potential with the interaction between inert molecules (a similar approach has also been discussed in [70]).…”
Section: Equation Of Statementioning
confidence: 99%